La Generación de Trayectorias Articulares para una Plataforma de Rehabilitación de la Fractura de Tobillo - Zamora Martínez, José Manuel; Rodriguez Liñan, Angel; Quiroz Compeán, Griselda; Cotri Melecez, Berenice (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
With the recent progress in care robots, the interest in the automatization of rehabilitation therapies has been increasing due to the benefits of personalized rehabilitation and the ease of performing rehabilitation without the need to leave home or have an expert throughout the entire process. Therefore, the present article proposes a methodology capable of generating the desired trajectories needed to conduct a proper ankle rehabilitation after suffering a fracture.